An Experimental Study to Assess the Effectiveness of Reminiscence therapy on the Level of Depression among Geriatrics in a WHO Society, Greater Noida, UP (International Journal of Nursing Education, 2019)
Aging is not a disease, but the final stage of normal life. “Old age is an incurable disease”. “You do not heal old age”, “you protect it”, “you promote it”, “and you extend it”. The degree of adaptation to the fact of aging is crucial to a man’s happiness in the phase of later life. Failure to adapt can result in bitterness, inner withdrawal, weariness of life and depression. The difficult changes that many geriatrics can lead to depression especially in those without a strong support system1. Purpose: The purpose of the study was to assess the effectiveness of Reminiscence therapy on the level of depression among geriatrics. Objectives 1.To assess the pre and post-test level of depression among elderly people in a selected society. 2. To evaluate the effectiveness of reminiscence therapy on the level of depression among elderly people in a selected society.3.To associate the post level of depression among elderly people with their selected demographic variables (age, sex, marital status, education, religion, source of income, type of family, number of children, habitant and history of physical illness.) Methodology: The research design was Pre-experimental one group pre-test and post-test design7, the setting chosen to conduct study was a WHO Society, Greater Noida, UP201306. The sample was geriatric peoples of age 60-80yr, Sample size was 50, The sampling technique used was purposive sample technique7. The geriatric peoples who fulfilled the inclusion criteria were selected as samples and were given Reminiscence therapy. The scale adapted to measure geriatric depression was a standardised Geriatric depression scale with 30 dichotomous type questions with yes or no response2. The interpretation of the score cut-off; Normal 0-9, Moderate depressive 10-19, and severe depressive 20-30.The data gathered and analysed by using descriptive and inferential statistics method and interpretation is made on the basis of objectives of the study. Major findings: The analysis of the study findings revealed that the pre-test mean was 13.08 with a standard deviation of 5.094 and the post-test mean was 7.54 with a standard deviation of 2.70. The paired calculated value of t=10.28 was found to be highly statistically significant at p<0.02. Chi square test revealed that there is no association between the demographic variables. Conclusion: The study infers that there was highly statistically significant reduction in the level of depression among the geriatrics after providing the reminiscence therapy on depression to the geriatric